THE REFLECTION OF HUMANISM IN SIR THOMAS MORE’S UTOPIA AND ALISHER NAVOI’S HUMANISTIC PHILOSOPHY - Ajikulova Ayajan Rinatovna.Khamitov Eldorbek Erkinovich (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
ABSTRACT This article explores the reflection of humanism in Sir Thomas More’s Utopia and Alisher Navoi’s Mahbub ul-Qulub, emphasizing how both authors, despite belonging to different cultural and religious traditions, share a unified moral vision. The study analyzes how More’s Christian humanism and Navoi’s Islamic mysticism converge on similar ideals of justice, education, compassion, and moral reform. More’s Utopia presents a rational and equal society governed by moral law, while Navoi’s Mahbub ul-Qulub advocates ethical governance, the pursuit of knowledge, and the cultivation of human virtue. Through a comparative lens, the paper highlights that both thinkers use literature as a means to promote human dignity and moral improvement, demonstrating that the core values of humanism transcend historical and cultural boundaries.